Triathlon: swimming for winning - Olbrecht, J. (Journal of Human Sport & Exercise, 2011)
Swimming performance in triathlon gradually gets of overriding importance in view of the final positioning in a race. It is important to end up swimming in the leading group(s) and to consider the impact of the swim stage on the 2 remaining sports disciplines in order to outbalance the athlete's effort and to be able to keep racing for a good position until the end of the race. Unlike cycling and running where the performance mainly depends on conditioning, the performance in swimming is a subtle combination of conditioning and technical abilities. Even elite swimmers may lose a lot of performance if their outstanding conditioning is not coupled with an excellent swimming technique. Triathletes very often suffer from a lack of technique and despite the wetsuit, which partially outbalances this shortcoming, they spend a lot of energy in the swim stage without reaping any success, energy which is then not on hand anymore for the rest of the race. Therefore, swimming technique should be the groundwork in the multi-year planning AND should be focussed on in each training session during the whole carrier of the triathlete. Monitoring the combination of time/stroke rate/stroke length is thus a must. Periodisation in triathlon is much more complex than in "single" sports. Not only the sports specific weaknesses/strengths of the athlete but also the intrinsic interaction between cycling, running and swimming on training effects and his swim-technical qualities will rule the periodisation. Additionally the level of technique will also set volume, intensity and form of training exercises. Simple to complex tests can help to make the right choice. This makes from triathlon an exciting sport, not only for the athlete but also for the coach and supporting teams. This article will summarise some practical implications on periodisation and on swimming training in triathlon.